Biosynthesis and isolation of selenoneine from genetically modified fission yeast. Issue 10 (24th September 2018) - Turrini, Nikolaus G.; Kroepfl, Nina; Jensen, Kenneth B.; Reiter, Tamara C.; Francesconi, Kevin A.; Schwerdtle, Tanja; Kroutil, Wolfgang; Kuehnelt, Doris
Abstract : Selenoneine was successfully purified from genetically modified Schizosaccharomyces pombe grown in selenate containing culture medium. Abstract : Selenoneine, a naturally occurring form of selenium, is the selenium analogue of ergothioneine, a sulfur species with health relevance not only as a purported antioxidant but likely also beyond. Selenoneine has been speculated to exhibit similar effects. To study selenoneine's health properties as well as its metabolic transformation, the pure compound is required. Chemical synthesis of selenoneine, however, is challenging and biosynthetic approaches have been sought. We herein report the biosynthesis and isolation of selenoneine from genetically modified fission yeast Schizosaccharomyces pombe grown in a medium containing sodium selenate. After cell lysis and extraction with methanol, selenoneine was purified by three consecutive preparative reversed-phase HPLC steps. The product obtained at the mg level was characterised by high resolution mass spectrometry, NMR and HPLC/ICPMS. Biosynthesis was found to be a promising alternative to chemical synthesis, and should be suitable for upscaling to produce higher amounts of this important selenium species in the future.